HUBUNGAN KECERDASAN EMOSIONAL DENGAN INTERAKSI SOSIAL PADA SISWA KELAS XI SMA INSTITUT INDONESIA SEMARANG - Niken Dwi Prameswari, Niken Dwi Prameswari; Handayani, Arri; Setiawan, Agus (Jurnal Psikoedukasia, 2026)
Abstract. This study is motivated by the low emotional intelligence and social interaction skills of eleventh-grade students at SMA Institut Indonesia Semarang, indicated by difficulties in recognizing and managing emotions, low self-confidence, and challenges in adapting to peers and teachers. The study aims to examine the relationship between emotional intelligence and social interaction. Using a quantitative correlational approach, the population consisted of 89 students, all sampled through saturated sampling. Data analysis with Pearson correlation revealed a significance value of 0.012 (<0.05) and a correlation coefficient of 0.265, indicating a significant positive but low relationship. The results suggest that higher emotional intelligence is associated with better social interaction. This study highlights the importance of developing students’ emotional intelligence to support healthy social interactions and foster a harmonious school environment.